2017
DOI: 10.1097/aci.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface lubricants

Abstract: The present state of ocular surface lubrication is slowly advancing from the routine use of cellulose-based solutions and gels to more advanced replacement with natural tear components. The advances that are occurring on other lubricating surfaces of the musculoskeletal system are also providing some insights into potential use on the ocular surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…HA is a well investigated polymer in the ophthalmic field. HA is the highest-selling artificial tear ingredient 17 . The epithelial healing and anti-inflammatory effect of HA has been repeatedly reported 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…HA is a well investigated polymer in the ophthalmic field. HA is the highest-selling artificial tear ingredient 17 . The epithelial healing and anti-inflammatory effect of HA has been repeatedly reported 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Lubricin is a mucin-like proteoglycan that has been found in various tissue compartments, including synovial fluid [151] and the eyes [152]. Many in vitro and in vivo studies have found lubricin to have anti-adhesive and anti-inflammatory properties [153].…”
Section: Lubricinmentioning
confidence: 99%
“…70,71 Medications Topical therapies for ocular allergy are outlined in Table 5, Table 6 and Table 7. [70][71][72][73][74][75][76][77][78][79][80][81]…”
Section: Avoidance and Nonpharmacologic Measuresmentioning
confidence: 99%